2015
DOI: 10.1080/13102818.2015.1046404
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional finite-element analysis of a single implant-supported zirconia framework and its effect on stress distribution in D4 (maxilla) and D2 (mandible) bone quality

Abstract: The aim of this in-silico study was to compare stress distributions in implants and zirconia frameworks of mandibular and maxillary implant-supported crowns. For comparison, vertical and oblique loading forces were used. Three-dimensional finite-element implant models of a mandibular section of bone (D2) and a maxillary section of bone (D4) with missing second molars and their zirconium-based superstructures were used. Zimmer dental implants of 13 mm in length and 4.7 mm in diameter were modelled. A load of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
2
0
0
1
Order By: Relevance
“…The results in this work demonstrated, as well as several researches using biomechanical analysis by the finite element method such as those by Silva et al (2014), Guven et al (2015), Kaleli et al (2017), Alvarez-Arenali et al (2017) and Arinc (2018), that oblique loads generate a higher concentration of stress in the entire implant/crown set (26,31,28,4,29). In addition, it was observed that the highest stress concentration on the implant was located in the neck region and inside its platform, that is, in the transition area between implant and crown, reinforcing the results obtained by Goodacre et al (2003) and Demachkia et al (2022) (32,33).…”
supporting
confidence: 82%
“…The results in this work demonstrated, as well as several researches using biomechanical analysis by the finite element method such as those by Silva et al (2014), Guven et al (2015), Kaleli et al (2017), Alvarez-Arenali et al (2017) and Arinc (2018), that oblique loads generate a higher concentration of stress in the entire implant/crown set (26,31,28,4,29). In addition, it was observed that the highest stress concentration on the implant was located in the neck region and inside its platform, that is, in the transition area between implant and crown, reinforcing the results obtained by Goodacre et al (2003) and Demachkia et al (2022) (32,33).…”
supporting
confidence: 82%
“…Based on the Hounsfield unit, Misch [35] classified bone density into four types-D1, D2, D3 and D4 [36]. It is proven that more stresses are generated in D3 and D4 bone compared to D1 and D2 bone [26,37]. In the present study, also, higher stress was seen in the D4 bone than in the D2 bone [Figure 12].…”
Section: Discussionsupporting
confidence: 52%
“…O tipo do elemento selecionado para uso deve ser capaz de representar o verdadeiro comportamento físico do modelo com a maior aproximação possível ao sistema real (ARAT BILHAN et al, 2015;BULAQI et al, 2015a;GUVEN et al, 2015;HASAN et al, 2015;TORCATO et al, 2014 ABUHUSSEIN et al, 2010;AYLLÓN et al, 2014b;DUNDAR et al, 2016;FAEGH;MÜFTÜ, 2010;HERNANDEZ-RODRIGUEZ et al, 2015;LEE et al, 2010;LIN et al, 2009;PAN et al, 2015;SHEMTOV-YONA et al, 2014c;WOLFF et al, 2014). A idéia foi aplicar condições de restrição de movimentos para simular condições reais na seção da mandíbula.…”
Section: Discretização E Seleção Do Tipo De Elementounclassified